P06.01 Bispecific antibody-driven synthetic agonistic receptor – transduced T cells mediate specific and conditional therapy in melanoma cancer models. (1st October 2020) - Benmebarek, M; Keyl, J; Märkl, F; Geiger, M; Karches, C; Rausch, S; Gottschlich, A; Öner, A; Feinendegen, M; Dörr, J; Cadilha, B; Endres, S; et al.
Abstract : Background: Immunotherapeutic approaches, including immune checkpoint blockade and adoptive T cell therapy (ACT) in the form of tumor-infiltrating lymphocytes (TILs), have had marked success in the treatment of melanoma. Despite these successes, many patients are refractory to treatment or relapse with therapy-resistant disease. To overcome these limitations, we propose a controlled ACT approach, where T cells are armed with synthetic agonistic receptors (SARs) that are conditionally activated only in the presence of a target melanoma-associated antigen, and a cross-linking bispecific antibody (BiAb) specific for both (SAR) T cell and tumour cell. Materials and Methods: A SAR composed of an extracellular EGFRvIII, trans- membrane CD28, and intracellular CD28 and CD3z domains was fused via overlap- extension PCR cloning. T cells were retrovirally transduced to stably express our SAR construct. We validated our approach in two murine as well as two human cancer models expressing our melanoma-associated target antigens TYRP (murine) and MCSP (human). We confirmed conditional and specific stimulation and proliferation of our T cells, as well as their tumour-antigen-directed cytotoxicity, in vitro and in vivo . Results: Crosslinking TYRP-EGFRvIII (murine) and MCSP-EGFRvIII (human) BiAb, monovalently selective for our SAR, induced conditional antigen-dependent activation, proliferation of SAR-T cells and directed tumour cell lysis with specificity towards two TYRP-expressing murine melanoma and two MCSP-expressing human melanoma cancer models. In vivo, anti-tumoural activity was mediated by the co-administration of SAR-T cells and BiAb, in an A375 melanoma xenograft model. Further, overexpression of IDO (a key immunosuppressive enzyme implicated in the suppression of T cell function in the tumor microenvironment) in a melanoma model did not influence the killing kinetics of SAR T cells. Conclusions: Here we apply the SAR x BiAb approach in efforts to deliver specific and conditional activation of synthetic agonistic receptor transduced T cells, and targeted tumour cell lysis. The modularity of our platform is key for a targeting approach in a tumor entity with a high mutational load such as melanoma and is fundamental in our drive towards personalised immunotherapies. Further, the SAR approach has demonstrated resistance to IDO-mediated inhibition in the context of melanoma, an interesting axis that requires further investigation. Disclosure Information: M. Benmebarek: None. J. Keyl: None. F. Märkl: None. M. Geiger: A. Employment (full or part-time); Significant; Roche. C. Karches: None. S. Rausch: None. A. Gottschlich: None. A. Öner: None. M. Feinendegen: None. J. Dörr: None. B. Cadilha: None. S. Endres: None. C. Klein: A. Employment (full or part-time); Significant; Roche. S. Kobold: None.